Historical sources of honor protection, dignity and inviolability of person’s private life - Сосніна, Ольга Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The author of the given article appeals to such legal sources as Ruska Pravda, Church Statute Yaroslav, analyses their principles relatively available standards directing to honor protection, dignity and inviolability of private life and person’s dwelling